Carvacrol protects rat liver exposed to formaldehyde by regulating oxidative stress, and asprosin and subfatin hormones - Emre, E.; Ogeturk, M.; Aydin, S.; Kuloglu, T.; Aksu, F.; Kavakli, A. (Taylor & Francis Ltd, 2023)
Toxic doses of formaldehyde (FA) can cause oxidative damage and impair energy metabolism. Asprosin (ASP) and subfatin (SUB) are adipokines produced by adipose tissue that help regulate energy metabolism. We investigated the effects of carvacrol (CAR), an antioxidant with hepatoprotective properties, on ASP and SUB in rats exposed to FA using immunohistochemistry and biochemistry. We used 42 male Wistar albino rats divided into six groups of seven: group 1, untreated control; group 2, FA (10 ppm FA by inhalation 8 h/day, 5 days/week); group 3, CAR-20 (20 mg/kg); group 4, CAR-40; group 5, FA (10 ppm FA by inhalation 8 h/day, 5 days/week) + CAR-20 (20 mg/kg); group 6, FA (10 ppm FA by inhalation 8 h/day, 5 days/week) + CAR-40 (40 mg/kg). Levels of ASP and SUB, and total oxidant status (TOS) and total antioxidant status (TAS) in blood and liver tissue were measured using ELISA. ASP and SUB immunoreactivity was assessed using immunohistochemistry. The number of apoptotic cells was determined using the TUNEL method. The number of apoptotic cells in group 2 was increased compared to group 1. TOS in group 2 was increased compared to group 1. The numbers of apoptotic cells and TOS in group 3 were decreased compared to group 1. TOS was decreased in group 6 compared to group 2, but TOS was increased compared to group 1. We found ASP and SUB immunoreactivity in the liver. All alterations were reversed by addition of CAR. It appears that FA disrupts energy metabolism and CAR ameliorates the destructive effects of FA when used at appropriate doses, although CAR might be harmful at high doses.
Keywords: Asprosin; carvacrol; formaldehyde; hepatoprotection; hormones; liver; oxidative stress; rats; subfatin